2017
DOI: 10.1007/s00204-017-2114-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biotransformation of pyrrolizidine alkaloids in different species. Part I: Microsomal degradation

Abstract: Pyrrolizidine alkaloids (PA) are secondary metabolites of certain flowering plants. The ingestion of PAs may result in acute and chronic effects in man and livestock with hepatotoxicity, mutagenicity, and carcinogenicity being identified as predominant effects. Several hundred PAs sharing the diol pyrrolizidine as a core structure are formed by plants. Although many congeners may cause adverse effects, differences in the toxic potency have been detected in animal tests. It is generally accepted that PAs themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…In the previous studies, we demonstrated that liver microsomes from species considered to be sensitive to PAs showed a lower metabolic rate than liver microsomes from species considered to be more resistant (Kolrep et al 2018 ). This observation could be explained by the fact that the observed high overall rate of microsomal biotransformation in non-susceptible species mainly represents a detoxification.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the previous studies, we demonstrated that liver microsomes from species considered to be sensitive to PAs showed a lower metabolic rate than liver microsomes from species considered to be more resistant (Kolrep et al 2018 ). This observation could be explained by the fact that the observed high overall rate of microsomal biotransformation in non-susceptible species mainly represents a detoxification.…”
Section: Introductionmentioning
confidence: 84%
“…Although much research has focused on the identification of PA metabolites (Buhler and Kedzierski 1986 ; Fashe et al 2014 , 2015 ; Fu et al 2004a ), their quantification revealed that a large portion is still unknown. Furthermore, GSH-DHP conjugates like 7,9-diglutathionyl-6,7-dihydro-1-hydroymethyl-5H-pyrrolizidine (diGSH-DHP), and 9-glutathionyl-6,7-dihydro-1-hydroxymethyl-5H-pyrrolizidine (monoGSH-DHP) suggested as biomarkers for in vitro metabolic activation were not detectable when CYP content is low—for instance when using S9 as metabolic system instead of microsomes, or were only detectable after long-term incubation (Ebmeyer et al 2019 ; Geburek et al 2020 ; Kolrep et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasiocarpine has the shortest in vitro half‐life (10 min) in most species. In horses, intermedine and senkirkine have the longest half‐lives (>1400 min) . Intermedine and senkirkine were found in the feed products tested in the current study, but only at low levels.…”
Section: Discussionmentioning
confidence: 57%
“…In vivo acute toxicity studies show significant differences in the toxicity of individual pyrrolizidine alkaloids in rats and mice . Similarly, significant differences in pyrrolizidine susceptibility between species have been identified under in vitro conditions . In vitro transformation of intermedine, lasiocarpine, senecionine and senkirkine by liver enzymes have different half‐lives in humans and animal species such as pigs, horses, cows, goats, sheep, rabbits and rats.…”
Section: Discussionmentioning
confidence: 99%